Left atrial function is impaired in cardiac amyloidosis and other cardiomyopathies with hypertrophic phenotype: haemodynamic correlations, pathophysiological consequences and prognostic implications. (14th October 2021) - Palmiero, G; Rubino, M; Monda, E; Caiazza, M; Vetrano, E; Lioncino, M; Di Fraia, F; Dongiglio, F; Cerciello, G; Manganelli, F; Ascione, L; Caso, P; et al.
Abstract: Background: Left atrial function (LAF) is emerging as a novel determinant of clinical status and outcome in cardiomyopathies. However, few studies compare LAF between CA subgroups and between CA and other hypertrophic cardiomyopathies. Purpose: This study explores the LAF in cardiomyopathies with hypertrophic phenotype and between CA subgroups and its consequences on clinical status, haemodynamic consequences and survival. Methods: We enrolled 50 patients with CA (26 with AL and 24 with wild type ATTR form), 75 patients with LV hypertrophy (LVH) [25 with hypertrophic cardiomyopathy (HCM), 25 with hypertensive cardiomyopathy (HypCM), and 25 with aortic stenosis (AS)]. Besides routine echocardiographic measurements, we analysed LAF using the phasic method (LAEI as reservoi, LAPEF as conduit, LAAEF as pump and TLAEF as total emptying LA function). Results: The ATTR showed higher atrial dimensions with a significant reduction in the reservoir and total LA emptying function compared to the AL group (see Table 1). Instead, compared to the LVH group, CA patients showed higher atrial dimension with all LAF phasic parameters reduced, higher LV filling pressures and reduced biventricular function. Then, we further divided the CA and LVH group into subgroups based on the presence or absence of LA dysfunction (LADys+) defined as TLAEF values below the median [TLAEF <50, 2%; range 9, 3–70, 9%]. Patients in CA/LADys+ group showed the worst NYHA class, higher sPAP and lower values of TAPSE and TAPSE/sPAP ratio (see Figure 2). After a follow-up of 24 months, 19 patients died from cardiovascular causes [0/8 in CA/LADys-, 15/42 in CA/LADys+, 0/60 in LVH/LADys- and 4/26 in LVH/LADys+ group; (log-rank χ 2 29, 6; p<0, 0001)]. To predict whether LAF could predict cardiovascular deaths sequential multivariate model was employed, and TLAEF was entered together with established clinical and echocardiographic parameters (NYHA class, LAVI, E/Em, sPAP, TAPSE and TAPSE/sPAP ratio). At the final backward analysis, LAVI, TAPSE/sPAP and TLAEF were the independent prognosticators for adverse events. Discussion: The LAF is significantly impaired in CA and associated with worst clinical status, higher incidence of RV dysfunction and higher LV filling and pulmonary pressure. Moreover, LADys is significant associated with higher cardiovascular mortality. LADys results from chronic pressure overload due to LA's exposition to the higher LV diastolic pressure due to impaired LV compliance, and from direct infiltration in CA The result is a progressive LA remodelling with an increased LA pressure and consequenT backward transmission to the pulmonary venous system and to RV. Conclusions: The TLAEF is a novel parameter of LAF that correlates with increased pulmonary vascular resistance and RV dysfunction. It seems a promising novel prognosticator and amarker of the haemodynamic consequences of LADys. FUNDunding Acknowledgement: Type of funding sources: None.